Optimization of Categorization of Card Payments - Dohová, Simona (2025)
This master's thesis focuses on identifying similarities between the names of uncategorized merchants and those already categorized, using various similarity metrics and evaluating their effectiveness. After selecting the most suitable metric, it explores methods for categorizing these similar merchants. First, it explores the suitability of a classification model using NLP (Natural Language Processing) for text vector representation. Additionally, it explores solutions using more advanced methods such as transformers. The analysis is conducted on real-world data from the largest financial institution in the Czech Republic. Its main purpose is to increase the coverage of categorized merchants to provide bank customers with a better understanding of their expenses.